A morphometric study to establish criteria for fetal and neonatal cerebellar hypoplasia: A special emphasis on trisomy 18. Issue 1 (16th December 2015) - Murakami, Ayumi; Tanaka, Mio; Ijiri, Rieko; Kato, Keisuke; Yamashita, Sumimasa; Kurosawa, Kenji; Arai, Nobutaka; Aoki, Ichiro; Tanaka, Yukichi
Abstract : Cerebellar hypoplasia (CH) is one of the congenital abnormalities of the central nervous system and is seen in several diseases and syndromes. This study was conducted in order to examine methods for evaluating CH in fetus and neonate because CH has been diagnosed without any morphometric criteria at autopsy. We sampled 140 autopsied cases including nineteen trisomy 18 (T18), four non‐T18 with presumed CH, and 117 control cases without any brain malformation. Statistical significance was present in the cerebellar weight and weight ratio of cerebellum per total brain between T18 and the control. The exponential regression models (ERM) showed that cerebral weight, cerebellar weight, and weight ratio of cerebellum per total brain increased gradually relative to gestational age in both T18 and the control. However, cerebellar weight and weight ratio of cerebellum per total brain of T18 showed growth delay with clear distinction between the two groups. The non‐T18 with presumed CH showed similar results. Body weight, total brain, and gestational age should be considered totally when evaluating fetal and neonatal cerebellar development. Furthermore, the ERM results may be useful to evaluate the cerebellar development of fetus and neonate at autopsy.